Antidiabetic and Antidyslipidemic Activity of Ethyl Acetate Fraction of Binahong Leaves in Streptozotocin (STZ)-induced Diabetic Rats - Yani Mulyani; Patonah Hasimun; Nida Putri Apriliyanti (Majalah Obat Tradisional, 2026)
Diabetes mellitus (DM) is a disease characterized by hyperglycemia and impaired glucose, protein, and fat metabolism due to insulin deficiency or resistance. In type 2 DM, insulin resistance potentially causes dyslipidemia through increased lipolysis and glucose production in the liver as well as reduced glucose absorption into cells. According to previous reports, the prevalence of dyslipidemia is relatively high, ranging from 72-85%. One of the plants that has the potential for antidiabetic and antidyslipidemic is binahong (Anredera cordifolia (Ten.) Steenis). Therefore, this research aims to determine the antidiabetic and antidyslipidemic activity as well as the effective dose of ethyl acetate fraction from ethanol extract of binahong leaves to reduce blood sugar levels, total cholesterol, triglycerides, LDL, IAP, increase HDL levels, and improve the histological profile of the pancreas and aorta. The experiment was conducted curatively using 30 rats divided into 5 treatment groups, namely normal (Na-CMC 0.5%), diabetic group (Streptozotocin 35 mg/kgBW), positive control (Simvastatin 10 mg/kgBW), and the test group given ethyl acetate fraction of ethanol extract at dose 1 (100 mg/kgBW) and 2 (150 mg/kgBW). All groups except normal received streptozotocin induction for 3 days until a diabetic rat model was formed, then the test drug treatment was given for 28 days. Blood sugar levels were measured on days 0, 3, 14, and 28 using a glucometer, and lipid profile levels were measured on days 0 and 28 enzymatically using a microlab 300. The results showed that the ethyl acetate fraction of binahong leaves ethanol extract at a dose of 100 mg/kgBW demonstrated antidiabetic and antidyslipidemic effects. It reduced blood glucose and lipid levels by 36–62% compared to the diabetic group and showed similar results to the positive control. This dose also improved the histological structure of the pancreas and aorta.